PROTECTIVE EFFECT OF WY14643 IN HEPATIC ISCHEMIA/REPERFUSION INJURY VIA SUPPRESSING THE ACTIVATION OF TLR4/NF-ΚB P65 SIGNAL PATHWAY. - Zhou, Yu-rong; Zhang, Jiong; wei-wei, He; Wang, Jia; Wang, Fang (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Hepatic ischemia/reperfusion (I/R) injury is a disaster common critical event which frequently occurs in a variety of clinicalscenarios. To investigate the protective effect of Wy14643 (WY) precondition against hepatic ischemia/ reperfusion (I/R) injury in rats and itspotential mechanism.Methods: Thirty Sprague–Dawley male rats weighing 220-250 g were randomly divided into three groups (n=10) including the sham-operated+saline group (Sham), the ischemic-reperfusion+ vehicle (IRI), and the WY14643 preconditioning group (WY). The three groups werepretreated with saline, ethanol and WY, at 1 h before ischemia with a concentration of 10 mg/kg , respectively. Hepatic ischemia-reperfusion(I/R) was induced by clamping blood supply to the left lateral and median lobes of the liver for 90 min. Blood samples and liver tissues wereobtained at the end of 4h reperfusion. The serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactatedehydrogenase (LDH) were measured. The histological changes of hepatic tissues were examanied by HE staining. The expression ofinterleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) were detected by ELISA and RT-PCR. Moreover, theexpression of TLR-4 , I-, Myd88, p65 and PPAR- were detected by western blotting.Result: After 4 h reperfusion, compared with the IRI group, the liver dysfunction (ALT, AST and LDH), damage score, the expressionof TNF-α , IL-6, and IL-1β, the protein expression level of TLR4, Myd88, the phosphorylation level of IκB- and p65 in the WY group wassignificantly decreased (all P<0.05); while the protein expression of IκB- was increased (P<0.05) with no difference in the expression of p65(P>0.05) .Conclusion: Wy14643 precondition could protect liver againest I/R injury and the protective effect is associated with suppressing inflammationby reducing the activation of TLR-4/NF- signaling.